Tingkat Kerusakan DNA Spermatozoa Memengaruhi Profil Protein Spermatozoa pada Semen Beku Sapi Brahman (LEVEL OF SPERMATOZOA DNA DAMAGES AFFECTS SPERMATOZOA PROTEIN PROFILES IN BRAHMAN BULLS FROZEN SEMEN) - Priyanto, Langgeng; Budiyanto, Agung; Kusumawati, Asmarani; Kurniasih, Kurniasih (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.512, 2019)
The purpose of this study was to investigate the relationship between spermatozoa DNA damages with spermatozoa protein profiles of after freezing. The rate of spermatozoa DNA damages was measured by Sperm-Bos-Halomax from two Brahman bull straw samples and the spermatozoa protein was isolated by separating the upper and lower fractions of the centrifugation results. The protein profiles were then analyzed using SDS PAGE with a 12.5% separating gel concentration. The data obtained were analyzed descriptively by comparing level of spermatozoa DNA damages with spermatozoa protein profiles of upper and lower fractions. The results of the analysis showed that in the upper fractions at 37.11% level of spermatozoa damages, one protein band (29 kDa) and at 10.66% level of DNA spermatozoa damages 9 protein bands (128 kDa, 110, 91, 55, 44, 29, 27, 25 and 20 kDa) were found, respectively. Meanwhile, in the lower fractions of frozen semen, at 37.11% level of spermatozoa DNA damages 4 protein bands (105, 82, 56 and 25 kDa), and at 10.66% level of spermatozoa DNA damages 8 protein bands (109, 95, 79, 69, 50, 44, 24 and 18 kDa) were found, respectively. It can be concluded that there are differences in the spermatozoa protein profiles between different levels of spermatozoa damages.